TRUMP’S DECISION TO RECOGNIZE JERUSALEM AS ISRAEL’S CAPITAL: DOMESTIC MOTIVATIONS AND REGIONAL CIRCUMSTANCES - Aljamal, Yousef M. (Journal of Al-Tamaddun, 2020)
One could claim that the US’s move of relocating embassy from Tel Aviv to Jerusalem after recognizing it as the capital of Israel would be likely impossible without the existence of specific domestic circumstances as well as regional developments. Trump wanted to get the support of the pro-Israel Republicans, to appease his pro-Israel Jewish donors, to win the support of his white Christian evangelical base, to over-shadow investigations against him in the US, to enforce his policy of isolationism, and to highlight his personal connections with Israel. The regional situation in the Middle East made taking such a decision an easier task for Trump, with Palestinians divided, Arabs ready to accept Israel like no time before, and some Arab governments already in process of normalizing ties with Israel at a time when the Arab countries are busy with their own domestic issues following the outbreak of the Arab Spring and civil wars in 2011. All these factors paved the way for Trump to break a taboo in the US foreign policy that was maintained by all former American presidents, thus angering Palestinians and pleasing Israelis.